Which Biology Marker Can be a Predictor for Higher Syntax Score? - Linda Lison; Irawan Yusuf; Bambang Sutrisna; Peter Kabo; Teguh Santoso; Ferry Sandra (The Prodia Education and Research Institute (PERI), 2014)
BACKGROUND: Syntax score is a lesion-based angiographic scoring system, originally devised to grade the anatomic complexity of coronary artery disease (CAD) and thereby facilitate consensus in the study of a diagnostic angiogram between surgeons and interventional cardiologists. Suitable biology marker to predict the severity of CAD and to have a treatment decision for revascularization by percutaneous coronary intervention (PCI) or bypass surgery, is still unknown. Which biology marker can be a predictor for higher Syntax score remains unknown as well.METHODS: Severity of 105 patients who underwent coronary angiography, were evaluated with Syntax score. Laboratory tests were conducted for routine blood test, serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), high-sensitivity C-reactive protein (hs-CRP), total cholesterol, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides, kidney function, creatinine and hemoglobin A1c (HbA1c).RESULTS: Ureum had significant correlation with Syntax score, p=0.016 and 95% confidence interval (CI)=0.05-0.55. Result of logistic regression analysis showed that HDL and haematocrit had significant correlation with Syntax score, with cut off point 34 (p=0.02, p=0.0033, respectively). Based on multi-variate analysis, Syntax score 34 = 16 (HDL ≤40 + Ureum ≥23) + 10 (Neutrophil/Lymphocyte ≥3.789) +10 (HbA1c ≥7 ) + 13 ( monocyte ≥9%).CONCLUSION: HDL cholesterol, ureum, neutrophil-lymphocyte ratio, HbA1c and monocyte altogether can predict the higher Syntax score.KEYWORDS: syntax, neutrophil, lymphocyte, HDL, cholesterol, ureum, HbA1c, monocyte